Exploring linguistic patterns and engagement in digital narratives: A computational analysis of 'Clues' - Pozharytska, Olena; Morozova, Iryna (Research Journal in Advanced Humanities, 2025)
This article explores the linguistic patterns and engagement strategies present in Robert Kendall's digital narrative "Clues." Utilizing a computational analysis framework and advanced text analysis software, we extract and categorize linguistic features to uncover patterns that enhance our understanding of narrative structure and style in digital formats. We examine the complexity of sentences within the text, categorizing them according to the classification system proposed by Ukrainian scholars Iryna Morozova and Olena Pozharytska. The analysis distinguishes between simple sentences, compound and complex sentences, and complicated sentences, highlighting the narrative's structural intricacies. By analyzing the use of grammatical constructions, such as grammatical complexes, homogeneous sentence members, and prolonged direct addresses, we aim to uncover how these linguistic features contribute to reader engagement and the overall effectiveness of the narrative. This study enhances our understanding of Kendall's work and provides insights into the broader implications of linguistic choices in digital storytelling.